Research on power trade potential and power balance between Lancang-Mekong countries and southern China under long-term operation simulation - Hao, Zhang; Hai, Lu; Enbo, Luo; Yanting, Huang; Zhi, Wu; Chong, Tang; Wenmeng, Zhao; Guo, Xie (Frontiers in Energy Research, 2023)
In order to further promote the interconnection development and construction of the power grids between the Lancang-Mekong countries and Southern China region and facilitate multilateral energy interaction, an assessment mechanism of the power balance and power trade potential between the two areas under long-term operation simulation is proposed. The mechanism first analyzes the energy supply structure, energy use forms, cross-border transmission capacity, and multi-area power trade potential of the power grids of the Lancang-Mekong countries and Southern China. Secondly, a power and electricity optimization model considering the long-period operation characteristics of generating units and regional interconnection transmission constraints is constructed, which can optimize the solution of a typical time-series operation scenario of 8760 h a year and improve the accuracy of regional power trade potential analysis. The results show that the Lancang-Mekong countries and the southern region of China have a significant potential for power trading, and the construction of a unified power trading market is vital for promoting the optimal allocation of power resources, achieving power balance, increasing the proportion of energy consumption, and reducing the cost of electricity consumption.